IMPLEMENTASI PENDIDIKAN KARAKTER DISIPLIN DENGAN MEMBERI IDENTITY CARD DI KELOMPOK A - Ahmad Farid Utsman; Umi Hanifah (Abata : Jurnal Pendidikan Islam Anak Usia Dini, 2021)
This study aims to determine the Discipline Character Education Learning. This research is a qualitative descriptive study. Located at RA Islamiyah Bulaklo. Data were collected by observation, interviews, and documentation. The data that has been collected is checked for validity by source triangulation and technical triangulation. Analyzed with interactive analysis techniques, namely data collection, data reduction, data presentation, and verification or conclusions. Research informants are the head of the foundation, principal, teachers, and guardians of students. The results showed that by giving Id Cards, students could line up neatly, put shoes and bags in their place according to the order on the Identity card which made students more disciplined and patiently waiting for their turn. From this study, it can be concluded that in the implementation of character education for early childhood (4-5 years) at RA Islamiyah Bulaklo in implementing character education using habituation activities starting from the child entering the gate until going home from school. For habituation activities such as marching, praying, memorizing Asmaul Husna, washing hands, and so on, by giving understanding to children, always be patient waiting for their turn according to the number on the Identity Card.